The Bight Basin, Evolution & Prospectivity I: gravity, deep seismic & basin morphology. Issue 1 (1st December 2019) - Cunneen, Jane; DePledge, Chanel; Lowe, Sharon; Hill, Kevin; Godfrey, Candice; Buckingham, Amanda; Farrington, Rebecca
Summary: Definition of the basement architecture within the Ceduna Sub-basin is poorly understood due to the depth of the basin and limited deep crustal geophysical datasets. This study uses seismic interpretation of BightSPAN™ deep crustal seismic lines combined with 2D forward models of the gravity to define the basement architecture in the Ceduna Sub-basin. Gravity forward models identify two depocentres with maximum depths of 25 km overlying thinned continental crust. Syn-rift sedimentary packages are several km thick and underlie up to 10 km of postkinematic Cretaceous deltaic sequences. Regional Moho models contain only sparse data points offshore and isostatic residual gravity data suggests substantial local variation in the depth to Moho. This local variation in the Moho surface is interpreted as boudinage of a weak lower crust along crustal shear zones. A gradual increase in basement density towards the continent-ocean transition suggests a diffuse rather than distinct boundary between continental and oceanic crust. The results of this work are used to constrain the tectonic evolution, particularly in terms of the subsidence history and uplift and erosional pulses recorded on the seismic data in the Ceduna Delta (Hill et al., this volume) and then used as input for finite element numerical models of rifting (Farrington et al., this volume).